THE ANALYSIS OF THE SPEECH “WHAT ISLAM REALLY SAYS ABOUT WOMEN” BY ALAA MURABIT BASED ON THE PERSPECTIVE OF LINGUISTICS BEHAVIORISM - Lula Wahyu Anindita; Ubaidillah (University of Muhammadiyah Malang, 2024)
This study aims to explain the analysis of the meaning of a speech context delivered by Alaa Murabit in the speech